Curriculum Expectations versus Teachers' Opinions and Practices in Teaching English in Rural Primary Schools in Uganda. Issue 2 (4th May 2019) - Ssentanda, Medadi; Southwood, Frenette; Huddlestone, Kate
Abstract: The expectation of the National Curriculum Development Centre (NCDC) of Uganda is that, using a thematic curriculum, learners in rural schools will learn at least 800 English words after three years of instruction in the language as a subject. This article draws on available literature on vocabulary learning by children and on results from a study conducted in four rural Ugandan primary schools. The study focused on the difficulties that learners in rural Ugandan schools experience in learning English, and the findings indicate that the expectation of acquiring 800 words in three years is unrealistic. The reasons for the failure to reach the 800-word target include a lack of availability of learning and teaching support materials, rural learners' limited exposure to English inside and outside of the classroom, teachers' low levels of English proficiency, and the limited time allocated to learning English. Recommendations are made for revisions to the curriculum and for improved support for teachers.